Effects of Innovation, Total Quality Management, and Internationalization on Organizational Performance of Higher Education Institutions - Texeira-Quiros, Joaquín; Justino, Maria do Rosário; Antunes, Marina Godinho; Mucharreira, Pedro Ribeiro; Nunes, António de Trindade (Frontiers in Psychology, 2022)
The aim of this research is to analyze the effects of innovation strategies, Total Quality Management (TQM) dimensions, and internationalization strategies that Higher Education Institutions (HEIs) might adopt, and their effects on their organizational performance. Due to globalization and the constant changes and demands that have taken place today, HEIs are forced to seek new quality assurance instruments in higher education, to ensure greater competitiveness in the markets and their survival. To examine the association between the independent variables, namely, TQM dimensions, innovation strategies, and internationalization strategies with the dependent variable, that is organizational performance of HEIs, we have chosen to use multiple linear regression analysis. A nine-predictor multiple linear regression model was proposed. The nine predictor variables are Communication, Involvement/teacher empowerment, Development/Teacher training, Continuous improvement, Leadership/Administration’s Commitment, Data analysis/Measurement of results, Focus on students, Innovation Strategies, and Internationalization strategy. We conclude that some TQM variables have a significant association with the organizational performance of HEIs, namely, Involvement/teacher empowerment, and Development/teacher training. On the other hand, also the Innovation strategies and Internationalization strategy have a significant association with the organizational performance of HEIs. This research is of enormous importance for the study of HEIs, considering their role in the development of any country and its impact on society as creators of knowledge and science. Since these institutions increasingly must deal with extremely competitive market environments, knowledge of the factors that can assist in increasing the organizational performance of HEIs is of great relevance.